Rule of Law, Institutional Quality and Information - Randolph Luca Bruno (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
The focus of this paper is the analysis of the persistent lawlessness attitude observed in some transition and developing countries where an overall increase in the quality of institutions is recorded. The mechanism of information diffusion on institutional quality is explored using a model where the state confronts a continuum of agents prone to either strip assets or to invest. The model predicts that high uncertainty and potential sunk costs in a situation of rule of law enforcement push the economy towards anarchy, a Pareto-dominated equilibrium. Viceversa, if the assets' value and the cost of asset-stripping are high, this is instrumental to a rule of law enforcement, a Pareto-dominant equilibrium. High institutional quality can increase the likelihood of rule of law enforcement if there is enough information about the strength of institutions. On the other hand, if good institutions and good information about institutions do not come together, there is scope for the puzzled co-existence of advancement in reforms and poor property rights protection.
Keywords: 330